Quality Improvement of Batik Packaging in Kalinyamat Wetan Village Tegal City - Endang Sulistianingsih; Deddy Prihadi; Sri Mulyati; Tika Maulida; Sanday Jamaludin (Universitas Pancasakti Tegal, 2021)
Kalinyamat Wetan is one of the villages located in Tegal City, Central Java, Indonesia. Based on observations made by the community partnership program of Pancasakti Tegal University there are problems faced by our partners, namely: 1) the uneven economy of the residents of Kalinyamat Wetan Village. In general, the economy of The People of Kalinyamat Wetan is good enough, but there are some poor people in Kalinyamat Wetan who need capital assistance and skills courses so that it can be used for entrepreneurship, 2) The problem of lack of knowledge about innovations in the field of Industry. The level of education is still relatively low in Kalimat Wetan which leads to a lack of information and knowledge about the latest innovations to developments in the field of Industry. To answer the problem, we provide solutions through providing training to batik craftsmen to improve the quality of their batik packaging. This is done so that there is an increase in the turnover of batik sales in order to increase their revenue. The implementation of community partnership program activities in the village of Kalinyamat Wetan Tegal city consisting of planning, action and evaluation in general went lancer and successful. Residents in the village of Kalinyamat Wetan, especially batik craftsmen have been able to make a variety of batik packaging designs and are able to provide product descriptions in attractive batik packaging. Residents responded to this PKM activity with great enthusiasm.